Necesidades de tratamiento en dentición primaria en niños de uno a cinco años con caries dental no tratada en una comunidad de bajos ingresos. Moravia, Medellín, 2006 Treatment needs in primary dentition in 1-5 year old children with non treated dental caries in a low-income community. Moravia, Medellín, 2006 - Blanca Susana Ramírez-Puerta; Gloria Escobar-Paucar; José Fernando Castro-Aguirre; Ángela María Franco Cortés (Revista Facultad de Odontología Universidad de Antioquia, 2009)
INTRODUCCIÓN: el objetivo fue establecer la prevalencia de caries dental no tratada y las necesidades de tratamiento en niños de uno a cinco años del barrio Moravia de Medellín. MÉTODOS: se realizó un estudio descriptivo transversal, en 162 niños. Un examinador calibrado (Kappa 0.73) evaluó el estado de la dentición de los niños -según criterios de Pitts y Fyffe, que establecen niveles de avance de las lesiones de caries dental (D1-D4)- y con base en este se determinaron las necesidades de tratamiento, teniendo en cuenta lineamientos actuales de un enfoque más preventivo. Los datos se analizaron en el programa SPSS 15.0; se estimó la proporción de niños con caries dental no tratada y el promedio de dientes para los diferentes tipos de tratamiento y sus desviaciones estándar. RESULTADOS: the gray tone scale varied from 0 to 255, corresponding to the value of the tones of pixels observable and dependent on electric current in Digital radiographic technology applied to maxillofacial area. CONCLUSIONES:la alta prevalencia de niños con caries de la infancia temprana (ECC) y lesiones de caries dental no tratada reflejan el problema de necesidades de atención acumuladas en esta población, lo cual hace evidente la relación de la caries dental con la inequidad y condiciones de vida que limitan el acceso a la atención odontológica oportuna y efectiva. INTRODUCTION: the purpose was to establish non treated dental caries prevalence and treatment needs in 1 to 5 year old children living in a low-income neighborhood in Medellin. METHODS: a cross-sectional study was performed in 162 children. A calibrated (Kappa 0.73) examiner assessed dental status according to Pitts & Fyffe criteria. Based on caries lesions advance (D1-D4), treatment needs were defined, according to current guidelines promoting a preventive and less invasive approach. The proportion of non treated dental caries was estimated, as well as the average and standard deviation of teeth per child requiring different treatment categories. RESULTS: from the total 162 children, 77.8% had non treated dental caries, each child having 5.8 ± 4.1 teeth needing some kind of treatment. From all dental caries lesions, 47% correspond to initial enamel lesions or small cavity confined to enamel (D1 - D2), potentially controlled by preventive treatment, and 53% compromise dentin and pulp (D3 - D4). Treatment needs increased with age. CONCLUSIONS: high prevalence of Early Childhood Caries and non treated dental caries lesions reflects cumulated treatment needs in this low income population and support a relationship between dental caries, inequalities and living conditions, limiting access to effective and opportune dental care.